2011
DOI: 10.1097/mbc.0b013e328346ef71
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene intron4 VNTR polymorphism in patients with chronic kidney disease

Abstract: Nitric oxide production is reduced in renal disease, partially due to decreased endothelial nitric oxide production. Evidence indicates that nitric oxide deficiency contributes to cardiovascular events and progression of kidney damage. A polymorphism in intron 4 of the endothelial constitutive nitric oxide synthase (ecNOS) gene is a candidate gene in cardiovascular and renal diseases. We investigated a potential involvement of this polymorphism in chronic renal failure. A case-control study involved 78 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…The present study explored two alleles in intron 4 of the eNOS gene that is reported to be a candidate gene in cardiovascular and renal diseases [23,24]. The larger allele (eNOS4b allele), designated 'b-insertion' has five tandem repeats, and the smaller allele (eNOS4a allele) 'a-deletion' has four repeats [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study explored two alleles in intron 4 of the eNOS gene that is reported to be a candidate gene in cardiovascular and renal diseases [23,24]. The larger allele (eNOS4b allele), designated 'b-insertion' has five tandem repeats, and the smaller allele (eNOS4a allele) 'a-deletion' has four repeats [21].…”
Section: Discussionmentioning
confidence: 99%
“…Determination of endothelial nitric oxide synthase genotypes eNOS genotype was determined using PCR [23,24]. Genomic DNA was extracted from peripheral blood using a QIAamp DNA Blood Mini Kit (Qiagen, GmbH, Hilden, Germany) and was stored at 48C until analysis.…”
Section: Diagnostic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…An impairment of nitric oxide production causes abnormalities in vascular function in many diseases including thrombosis, hypertension, atherosclerosis and renal disease (23,24). In the kidney, nitric oxide dilates renal blood vessels and modulates renin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…In Santos et al (26) study, the VNTR intron 4 a/b polymorphism was not associated with renal disease in Caucasian-Brazilians. Elshamaa et al (23) studied 78 children with chronic kidney disease (CKD) and 30 healthy controls. They showed that an allele was a high-risk allele for ESRD and this data were significantly different (p<0.05).…”
Section: Discussionmentioning
confidence: 99%